Corporate Governance in Germany: An Economic Perspective - Reinhard H. Schmidt (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2003)
A financial system can only perform its function of channelling funds from savers to investors if it offers sufficient assurance to the providers of the funds that they will reap the rewards which have been promised to them. To the extent that this assurance is not provided by contracts alone, potential financiers will want to monitor and influence managerial decisions. This is why corporate governance is an essential part of any financial system. It is almost obvious that providers of equity have a genuine interest in the functioning of corporate governance. However, corporate governance encompasses more than investor protection. Similar considerations also apply to other stakeholders who invest their resources in a firm and whose expectations of later receiving an appropriate return on their investment also depend on decisions at the level of the individual firm which would be extremely difficult to anticipate and prescribe in a set of complete contingent contracts. Lenders, especially long-term lenders, are one such group of stakeholders who may also want to play a role in corporate governance; employees, especially those with high skill levels and firm-specific knowledge, are another. The German corporate governance system is different from that of the Anglo-Saxon countries because it foresees the possibility, and even the necessity, to integrate lenders and employees in the governance of large corporations. The German corporate governance system is generally regarded as the standard example of an insider-controlled and stakeholder-oriented system. Moreover, only a few years ago it was a consistent system in the sense of being composed of complementary elements which fit together well. The first objective of this paper is to show why and in which respect these characterisations were once appropriate. However, the past decade has seen a wave of developments in the German corporate governance system, which make it worthwhile and indeed necessary to investigate whether German corporate governance has recently changed in a fundamental way. More specifically one can ask which elements and features of German corporate governance have in fact changed, why they have changed and whether those changes which did occur constitute a structural change which would have converted the old insider-controlled system into an outsider-controlled and shareholder-oriented system and/or would have deprived it of its former consistency. It is the second purpose of this paper to answer these questions.
urn:nbn:de:hebis:30-16651
Keywords: D21; D23; G30; L21; P51; 330; Corporate governance; Germany; complementarity; financial systems; stakeholders; Corporate Governance; Stakeholder; Institutioneller Wandel; Deutschland